Paciente de sexo masculino de 56 años con ulcera gástrica. - Bohórquez Sánchez, Geydy Carolina (2021)
The present clinical case is based on a 56-year-old male patient, who was diagnosed with gastric ulcer due to the presence of the Helicobacter pylori bacteria, has a family history (mother and sister) of stomach cancer and pancreatic cancer. , goes to the consultation for high intensity pain at the epigastria level, severe weight loss, lack of appetite, stomach bloating and burning, for this a nutritional assessment is carried out and it is determined through the BMI (muscle mass index) that the The patient is underweight (moderately thin), shows us a significant weight loss of 27%, additionally in his biochemical tests they show us hypertriglyceridemia, he is prescribed a normal caloric and hyperprotein diet, which aims to increase weight and mass muscular a list of foods that the patient may not eat is also sent to reduce the symptoms of said pathology, nutritional monitoring is carried out in conjunction with medical treatment. In the biochemical tests carried out later, it was observed that the triglyceride levels were normalized, finally a favorable result was obtained in their weight gain and gastrointestinal discomfort with the nutritional and dietary advice provided.